2017
DOI: 10.1159/000484573
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter, Randomized, Double-Blind, Placebo-Controlled Trial of Nalbuphine ER Tablets for Uremic Pruritus

Abstract: Background: Pruritus is a distressing hallmark of the uremic condition, affecting approximately 60% of hemodialysis patients. Abnormal endogenous opioid ligand activity at μ and κ-opioid receptors has been postulated as a mechanism in uremic pruritus. Nalbuphine is a μ-opioid antagonist and κ-opioid agonist. Methods: In this multicenter, randomized, double-blind, placebo-controlled trial, 373 hemodialysis patients with moderate or severe uremic pruritus were randomized in a 1: 1:1 ratio to nalbuphine extended-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 25 publications
1
57
0
1
Order By: Relevance
“…Nalbuphine, another novel therapy for pruritus, is a k‐opioid and μ‐opioid receptor antagonist. A multicenter, randomized, double blind, placebo‐controlled trial of 373 hemodialysis patients with moderate or severe uremic pruritus found that nalbuphine significantly reduced itching intensity among hemodialysis patients . In two studies naltrexone, a μ‐opioid receptor antagonist, yielded mixed results.…”
Section: Nonspecificmentioning
confidence: 99%
See 1 more Smart Citation
“…Nalbuphine, another novel therapy for pruritus, is a k‐opioid and μ‐opioid receptor antagonist. A multicenter, randomized, double blind, placebo‐controlled trial of 373 hemodialysis patients with moderate or severe uremic pruritus found that nalbuphine significantly reduced itching intensity among hemodialysis patients . In two studies naltrexone, a μ‐opioid receptor antagonist, yielded mixed results.…”
Section: Nonspecificmentioning
confidence: 99%
“…A multicenter, randomized, double blind, placebo-controlled trial of 373 hemodialysis patients with moderate or severe uremic pruritus found that nalbuphine significantly reduced itching intensity among hemodialysis patients. 42 In two studies naltrexone, a μ-opioid receptor antagonist, yielded mixed results. One study showed statistically significant benefit over placebo 43 while the other did not.…”
Section: Uremic Pruritusmentioning
confidence: 99%
“…In an open‐label study in 15 patients with CKDaP nalbuphine hydrochloride at doses of 180 or 240 mg twice daily exerted a reduction of itch intensity on a VAS from 4.0 to 1.2 and 0.8, respectively . A large randomized, placebo‐controlled trial in 371 patients on haemodialysis with moderate or severe CKDaP reported on a mild, but statistically significant NRS reduction in the 120 mg nalbuphine group of 3.5 compared to 2.8 in the placebo group after 8 weeks of therapy . In summary, the currently investigated κ‐opioid receptor agonists presented limited anti‐pruritic effects in RCTs.…”
Section: Introductionmentioning
confidence: 99%
“…Nalbuphine (NAL) has been recognized as a moderate‐efficacy partial agonist or antagonist of the μ‐opioid receptor and as a high‐efficacy partial agonist of the κ‐opioid receptor with its low affinity for either the δ‐opioid receptor or the σ receptor (Al‐Hasani & Bruchas, ; Barry & Zuo, ; Bodnar, ; Raghav, Jain, Dhawan, Roy, & Kumar, ). It can relieve moderate to severe pain and itching, the mechanisms are thought to be its binding to opioid receptors (Bodnar, ; Chen et al, ; Davis, Fernandez, Regel, & McPherson, ; Mathur et al, ; Pereira & Stander, ; Reszke & Szepietowski, ; Tubog, Harenberg, Buszta, & Hestand, ; Withey, Paronis, & Bergman, ). Alternatively, it can be used to balance anesthesia, for preoperative and postoperative analgesia, and for obstetrical analgesia (Bindra, Kumar, & Jindal, ; Kim, Kim, Lee, Chung, & Hong, ).…”
Section: Introductionmentioning
confidence: 99%
“…. It can relieve moderate to severe pain and itching, the mechanisms are thought to be its binding to opioid receptors (Bodnar, 2017;Chen et al, 2014;Davis, Fernandez, Regel, & McPherson, 2018;Mathur et al, 2017;Pereira & Stander, 2018;Reszke & Szepietowski, 2018;Tubog, Harenberg, Buszta, & Hestand, 2018;Withey, Paronis, & Bergman, 2018). Alternatively, it can be used to balance anesthesia, for preoperative and postoperative analgesia, and for obstetrical analgesia (Bindra, Kumar, & Jindal, 2018;Kim, Kim, Lee, Chung, & Hong, 2011).…”
mentioning
confidence: 99%